Law, love and freedom: from the sacred to the secular - Neoh, Joshua (Law and Christianity, 2019)
How does one lead a life of law, love, and freedom? This inquiry has very deep roots in the Judeo-Christian tradition. Indeed, the divergent answers to this inquiry mark the transition from Judeo to Christian. This book returns to those roots to trace the twists and turns that these ideas have taken as they move from the sacred to the secular. It relates our most important mode of social organization, law, to two of our most cherished values, love and freedom. In this book, Joshua Neoh sketches the moral vision that underlies our modern legal order and traces our secular legal ideas (constitutionalism versus anarchism) to their theological origins (monasticism versus antinomianism). Law, Love, and Freedom brings together a diverse cast of characters, including Paul and Luther, Augustine and Aquinas, monks and Gnostics, and constitutionalists and anarchists. This book is valuable to any lawyers, philosophers, theologians and historians, who are interested in law as a humanistic discipline